Causes of family separation and barriers to reunification: Syrian refugees in Jordan. (21st August 2020) - Chandler, Hannah; Boothby, Neil; McNatt, Zahirah; Berrigan, Margaret; Zebib, Laura; Freels, Patricia Elaine; Alshannaq, Hamza; Majdalani, Noor; Mahmoud, Ahmed; Majd, Esraa
Abstract: Since 2011, the war in Syria has resulted in the displacement of 12.2 million people. Over 5.6 million have fled Syria to seek asylum in neighbouring countries, while 6.6 million have been internally displaced. Family separation, with significant psychological, social and economic implications, is a key concern for those who flee violence and cross international borders. This qualitative study sought to understand the causes of separation among Syrian families in Jordan and the obstacles to family reunification. Semi-structured, in-depth interviews were conducted with 85 Syrian refugee families identified as having separated family members. We present critical moments during migration when family separation occurs: (1) while fleeing Syria, (2) while residing in Jordan and (3) pre-existing separation due to work or travel that was exacerbated by the conflict. We also highlight the factors that perpetuate separation among families, preventing or delaying them from reuniting. These findings may help to inform more humane family reunification practices as well as identify future research and learning needs.